Investigation of structure and properties of composite material Al₂O₃-SiC obtained by electroconsolidation process - Vovk, R.V.; Prokopiv, N.M.; Chishkala, V.A.; Kislitsa, M.V. (Functional Materials, 2018)
The results of research of influence of structure and phase composition parameters on the microstructure, physico-mechanical and cutting properties of aluminum oxide-based composites obtained by electrosparking (electroconsolidation) are described. It has been established that formation of the composite structure due to introduction of SiC nanopowders into the micropowder of aluminum oxide makes it possible to improve the physical and mechanical properties and wear resistance of Al₂O₃ ceramics.